Influence of Microwave Irradiation on Calcium Sulphate Crystal Phase - YANG, XIAO-QING; HUANG, KA-MA; YANG, LI-JUN; JIA, GUO-ZHU (Asian Journal of Chemistry, 2010)
In present studies, a special experiment system was designed to obtain calcium sulphate crystal under the similar temperature-profile increase in microwave heating and traditional heating by water bath. The main products heated by water bath heating are calcium sulphate dihydrates, but a small quantity of calcium sulphate hemihydrates are detected with microwave heating. By multiphysics calculation and experimental measurement, the results show that this difference is not induced by non-thermal effect and calcium sulphate hemihydrates induced by hot spot during the microwave heating.